The Diversity and Uniqueness of Avifauna in Erek-Erek Geoforest at Ijen Geopark, East Java, Indonesia - Arif Mohammad Siddiq; Hari Sulistiyowati; Agung Sih Kurnianto; Afina Aninnas; Samsuri Samsuri (Universitas Gadjah Mada, 2023)
Erek-Erek Geoforest (EEG) is one of the Biosites of Ijen Geopark located at the eastern slope of Mount Ijen. This location has unique topography of highland forests restricted by mountain ridges. This topography creates dense vegetation and humid ecosystem supporting microhabitats for endemic birds. This study aims to investigate the diversity and uniqueness of avifauna in EEG based on the existing value of birds. The method used is a point count at three potential station for the presence of birds. The data collected are the bird species, individual number of species, and species existence based on conservation status, distribution, and protection status. Data analysis includes the Shannon Wiener diversity index (H’), Evenness index (E), and existence factor (Ef) of bird community. The results show there are 57 species of birds belonging to 46 genera and 31 families. The diversity of birds in EEG Biosite has a high value (H'=3.40) and also a high evenness value (E=0.84). The Ef value of birds in this area is 51.35, which means the uniqueness value is a medium category. There are three bird species that have the highest Ef value, i.e Arborophila orientalis (Ef=80.00), Pycnonotus bimaculatus (Ef=73.33) and Locustella montis (Ef=73.33). The three species are endemic to Indonesia, especially A. orientalis whose distribution is limited to the highlands of East Java. Based on the composition, diversity, and uniqueness of avifauna in the EEG, it becomes valuable information for the government, Ijen Geopark Manager, and local communities to manage EEG Biosite conservatively by maintaining the existence of avifauna and their habitats.